Relationship Analysis between Children Interests and Their Positive Emotions for Mobile Libraries’ Community Development in a Tsunami Area - HAMADA, Masatoshi (Qualitative and Quantitative Methods in Libraries; Vol 10 No 1 (2021): March Issue 2021, 2021)
During our refuge life caused by the Tsunami in Japan on 11th March 2011, the children have visited the mobile libraries. Our experiences recommend a community development with a focus on children positive emotions for their future dreams by using the mobile libraries against the negative context. However, children have various interests such as art, media and people even during their refuge life. In addition, few studies have focused on relationships between the children interests and the children positive emotions. Therefore, this study proposes a relationship analysis to classify the children, which strengthens the children positive emotions during their refuge life. Data are collected by a questionnaire from all elementary and junior high school students in Ishinomaki City, 11029 children of five to fifteen years old, within two years after the Tsunami in 2011, Japan. A combination of factor loading and text mining classifies the children according to four processing: 1. Grasp the structure of data, 2. Extraction of latent factors, 3. Classification of children interests into several types and 4. Connect free writing data into the classification by text mining. Thus, both quantitative and qualitative outputs are combined by the relationship analysis. The 11029 children are classified into 32 groups. The community development by the mobile libraries ought to consider the 32 groups, counting on not only the libraries’ property but also people such as children families and friends. In addition, comparing the relationships of the children in non-Tsunami area, Tokyo, results in that 16 groups are with specific in the Tsunami area.